Substitution Program in Indonesia and Australia as Health Promotion Model at Schools (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Obesity has been increasing as much as twice on age 6-12 years. The increase is happening both in Indonesia and Australia. The objective of this research is to construct a program model in Australia that can be substituted to be a health promotion model at School in effort to suppress child obesity. Research was conducted in 2014 with qualitative approach. Instruments used are as follow 1) Secondary data filling form 2) In depth interview guidence instrument 3) FGD (Focus Group Discussion) and BST (Brain Storming Technique). The informations were obtained by purposive and snowball technique. Data analysis by Miles and Huberman model. Substitution model is based on consideration that applied model has potential to be developed and other models whether internal or external ones in Indonesia. The model will be substituted by considering school condition and situation. School Health Unit (SKU) is a potential platform to promote health by these activities 1) Formal health education as taken place curricullum 2) Informal health education in forms of (1) health education information (2) Self health behaviour monitoring and control (3) Health promotion by doing healthy life (4) distribution of health education booklet to teachers and parents.